Defense Institution Building in Africa An Assessment - McNerney, Michael J. (RAND Corporation, 2016)
This report assesses U.S. efforts in defense institution building (DIB) in Africa and suggests possible improvements to planning and execution. It defines DIB and reviews some best practices from DIB and security sector reform experiences. It also highlights how DIB activities serve U.S. official strategic guidance for Africa.